Epidemic landscapes - Pawłowska, Krystyna (Turystyka i krajoznawstwo, 2021)
The Covid-19 coronavirus pandemic has continued for a year. Unexpectedly, the lives of people all over the world have changed dramatically. Consequently, landscapes, both natural and cultural, are also changing. Nobody knows how long the pandemic life will last and what the post-pandemic world will be like. Extraordinary pandemic experiences should be enlightening. Therefore, it seems worthwhile collecting and organizing them in order to create a basis for reflection in the future.The article is an attempt to sketch the issues of changes in the landscape caused by the pandemic, preceded by a reflection on the traces and consequences of earlier epidemics written in art and left in the landscape. The list of questions that could be asked here from the experience of the pandemic is certainly not exhaustive and not all the questions asked are answered. The text is therefore not a research report, but rather an invitation to discussion.There are many places whose landscape has been changed by the pandemic, but perhaps the biggest concern tourist destinations from which tourists have disappeared. The debate on the scale and form of tourism can and should benefit from these experiences.